Norm Entrepreneur, Catalyst or Challenger? India in the Nuclear Non-proliferation Narrative. (March 2014) - Kumar, A. Vinod
The history of India's interaction with the normative structures of the non-proliferation regime has been unique albeit tumultuous. The vibrancy of the roles and identities that India had attained in the normative churning of the regime is a useful case study to understand the dynamics of norm construction within the non-proliferation system. While the model of norm entrepreneurship can be used to explain this phenomenon, the Indian example shows that the spectrum of the term 'agency' can transcend the existing understanding of norm entrepreneurship. The article uses India's non-proliferation history to examine how actors, based on their conceptions of interest and driven by various systemic factors, influence the norm construction process through different role identities.